Perceptions and health beliefs of Greek nursing students about breast self‐examination: A descriptive study. Issue 6 (14th April 2014) - Lavdaniti, Maria
Abstract : Breast self‐examination is a screening option for young women. Among students, knowledge about breast self‐examination ranges from insufficient to average. This descriptive study was planned in order to determine the health beliefs and perceptions of nursing students regarding breast self‐examinations. We recruited 538 nursing students in a single Higher Technological Educational Institute in Greece. Data were collected using the Champion's Health Belief Model Scale. Parametric tests were used in the data analysis. We found significant differences in the results of the subscales of Champion's Health Belief Model Scale on comparing people with respect to nationality, previous education about breast self‐examination, smoking status and semester in which they were studying. The 'confidence' subscale was positively associated with the frequency of breast self‐examination. The results of the present study demonstrated that nursing students have knowledge about breast‐self examination but inadequate practice.